2019
DOI: 10.1017/dmp.2019.17
|View full text |Cite
|
Sign up to set email alerts
|

National Assessment of Nursing Schools and Nurse Educators Readiness for Radiation Emergencies and Nuclear Events

Abstract: Nurses will play a crucial role in responding to a public health emergency resulting from nuclear war or other large-scale release of radiation into the environment and in supporting the National Health Security Strategy. Schools of nursing are ultimately responsible for developing a competent nursing workforce prepared to assess a population’s public health emergency needs and respond to these low-frequency but high-impact events. This responsibility includes the provision of specific content and training reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Among the reasons for the exclusion of 25 articles from the qualitative synthesis were; the research was not conducted empirically (e.g., review or report) or the main focus of the research was not on the impact of health crises on school populations. For example, a study by Veenema et al was excluded because the study only discussed nursing school and nursing educator preparedness for radiation emergencies [ 30 ], while the impact of nuclear events on the school population was not discussed or measured in the study. The flow of this systematic review process is explained in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Among the reasons for the exclusion of 25 articles from the qualitative synthesis were; the research was not conducted empirically (e.g., review or report) or the main focus of the research was not on the impact of health crises on school populations. For example, a study by Veenema et al was excluded because the study only discussed nursing school and nursing educator preparedness for radiation emergencies [ 30 ], while the impact of nuclear events on the school population was not discussed or measured in the study. The flow of this systematic review process is explained in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Sentinel events or natural disaster emergencies are especially relevant to this field (Green & Polk, 2009). Studies by Goodwin and colleagues have deepened the nurse's role in radiation treatment, nuclear disasters or Zika infection in pregnant women (Lavin et al, 2019;Veenema et al, 2019;Veenema & Thornton, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies of mapping capabilities related to disaster risks indicated there is considerable publicly available data on environmental hazards and natural disasters, but a lack of knowledge of the risks and necessary response by healthcare providers [ 32 , 33 , 34 ]. For example, Veenema et al [ 34 ] identified a full list of U.S. nuclear power sites, including nuclear power reactors and nuclear research and test reactors. [US Nuclear Regulatory Commission].…”
Section: Introductionmentioning
confidence: 99%
“…The faculty (18%) said they would teach it if there were content developed by experts. A total of 53% of respondents answered incorrectly when asked if they were within an emergency planning zone of a nuclear reactor [ 34 ].…”
Section: Introductionmentioning
confidence: 99%